Lifetime vs. rate capability: Understanding the role of FEC and VC in high-energy Li-ion batteries with nano-silicon anodes - Jaumann, Tony (2017)
Fluoroethylene carbonate (FEC) and vinylene carbonate (VC) are the most frequently used electrolyte components to enhance the lifetime of anode materials in Li-ion batteries, but for silicon it is still ambiguous when FEC or VC is more beneficial. Herein, a nanostructured silicon/carbon anode derived from low-cost HSiCl3 is tailored by the rational choice of the electrolyte component, to obtain an anode material outperforming current complex silicon structures. We demonstrate highly reversible areal capacities of up to 5 mA h/cm2 at 4.4 mg/cm2 mass loading, a specific capacity of 1280 mA h/gElectrode, a capacity retention of 81% after 500 deep-discharge cycles versus lithium metal and successful full-cell tests with high-voltage cathodes meeting the requirements for real application. Electrochemical impedance spectroscopy and post-mortem investigation provide new insights in tailoring the interfacial properties of silicon-based anodes for high performance anode materials based on an alloying mechanism with large volume changes. The role of fluorine in the FEC-derived interfacial layer is discussed in comparison with the VC-derived layer and possible degradation mechanisms are proposed. We believe that this study gives a valuable understanding and provides new strategies on the facile use of additives for highly reversible silicon anodes in Li-ion batteries.